Penerapan Strategi Pembelajaran Melalui Display Kelas dalam Upaya Mengatasi Rasa Jenuh Anak dalam Belajar pada Tingkat MI/SD - ., Rosidah (As-Sibyan, 2018)
This study discusses learning strategies through class display. This researchis literature research. Data obtained from several journals and some literature thatserve as the main source in completion of this research. The results showed thatlearning strategies through class displays can overcome the child's saturation whenthe learning process takes place. This class display is the ways or steps that must bedone by the teacher in conveying information or messages visually as attractive andcommunicative as possible so that they are easy to understand and students do notfeel bored quickly in learning, so in this case the teacher is required to have morecompetence in applying this class display. In applying this class display all mustspeak like teachers especially, class walls, windows, wall clocks, chairs, tables,bookshelves, etc. even the seragama that is used by the teacher and students mustspeak. Speaking in the sense that all things in the class must have meaning forstudents, not just a class used to take shelter while studying. According to MunifKatib, class display is capable of being a barometer of teacher creativity, teachingteacher quality, encouraging student learning, students' courage to appear in class,aesthetic sensitivity training, barometer of teacher and student collaboration, aspromotional material, because this class displays in addition to overcoming childboredom in learning, will also produce work. While the strategy itself has the meaning of setting plans or steps, while learning is an interaction between students and educators in teaching and learning activities. So if combined then the learning strategy is a series of plans or activities that have been prepared to achieve certain goals in the learning process.